From Farm to Table: Follow-Up of Shiga Toxin-Producing Escherichia coli Throughout the Pork Production Chain in Argentina - Colello, Rocío; Cáceres, María E.; Ruiz, María J.; Sanz, Marcelo; Etcheverría, Analía I.; Padola, Nora L. (Frontiers in Microbiology, 2016)
Pigs are important reservoirs of Shiga toxin-producing Escherichia coli (STEC). The entrance of these strains into the food chain implies a risk to consumers because of the severity of hemolytic uremic syndrome. This study reports the prevalence and characterization of Shiga toxin-producing Escherichia coli (STEC) throughout the pork production chain. From 764 samples, 31 (4.05%) were stx positive by PCR screening. At farms, 2.86% of samples were stx positive; at slaughter, 4.08% of carcasses were stx positive and at boning rooms, 6% of samples were stx positive. These percentages decreased in pork meat ready for sale at sales markets (4.59%). From positive samples, 50 isolates could be characterized. At farms 37.5% of the isolates carried stx1/stx2 genes, 37.5% possessed stx2e and 25%, carried only stx2. At slaughter we detected 50% of isolates positive for stx2, 33% for stx2e and 16% for stx1/stx2. At boning rooms 59% of the isolates carried stx1/stx2, 14% stx2e and 5% stx1/stx2/stx2e. At retail markets 66% of isolates were positive for stx2, 17% stx2e and 17% stx1/stx2. For the other virulence factors, ehxA and saa were not detected and eae gene was detected in 12% of the isolates. Concerning putative adhesins, agn43 was detected in 72%, ehaA in 26%, aida in 8% and iha in 6% of isolates. The strains were typed into 14 E. coli O groups (O1, O2, O8, O15, O20, O35, O69, O78, O91, O121, O138, O142, O157, O180) and ten H groups (H9, H10, H16, H21, H26, H29, H30, H32, H45, H46). This study reports the prevalence and characterization of STEC strains through the chain pork suggesting the vertical transmission. STEC contamination originates in the farms and is transferred from pigs to carcasses in the slaughter process and increase in meat pork at boning rooms and sales markets. These results highlight the need to implement an integrated STEC control system based on good management practices on the farm and critical control point systems in the food chain.